Historia de la Farmacoepidemiología en Cuba - Cruz Barrios, María (Horizonte Sanitario, 2021)
Object: To expose the main events that occurred in Cuba related with the development of the pharmacoepidemiology. Materials and methods: There was executed a bibliographical and documental revision of the topic in the national and international literature; the treatment of data was carried out by means of the analysis of content of direct type. Results: From its beginnings, the strategy of the pharmacoepidemiology in Cuba has performed several actions about education, information, investigation and management; among them it stands out the master of pharmacoepidemiology, the scientific production, the elaboration of documents rectors of the activity and the promotion of the rational use of medications to the Cuban population. Conclusions: The pharmacoepidemiology in Cuba contributes to facilitate the access of the medications with priority to that required according to the prevalent mortality indicators in the country.